Silencing of long non-coding RNA SDCBP2-AS1/microRNA-656-3p/CRIM1 axis promotes ferroptosis of lung cancer cells: LncRNA SDCBP2-AS1 affects ferroptosis of lung cancer cells - Dai, Ninghuang; Ma, Haitao; Feng, Yu (Cellular and Molecular Biology, 2023)
Long non-coding RNAs (lncRNAs) play central roles in lung cancer progression by acting as competing endogenous RNAs (ceRNAs). This study aimed to explore the roles of lncRNA SDCBP2-AS1 in lung cancer and the molecular mechanism. The expression of SDCBP2-AS1, microRNA (miR)-656-3p, and cysteine-rich transmembrane BMP regulator 1 (CRIM1) was measured using quantitative real-time polymerase chain reaction. Ferroptosis was evaluated by analyzing cell death, ferrous content, reactive oxygen species (ROS) level, and protein levels of ferroptosis markers. The binding relationship was assessed using a dual-luciferase reporter assay. We observed that SDCBP2-AS1 was highly expressed in lung cancer cells. Knockdown of SDCBP2-AS1 promoted ferroptosis of lung cancer cells. SDCBP2-AS1 is a sponge of miR-656-3p, which directly targets CRIM1. Rescue experiments confirmed that SDCBP2-AS1 regulates ferroptosis by miR-656-3p, and overexpression of CRIM1 abrogated the effects of miR-656-3p on ferroptosis. In conclusion, depletion of SDCBP2-AS1 promoted lung cancer cell ferroptosis via the miR-656-3p/CRIM1 axis.